Sustainable crop nutrition for ameliorating biotic stress in grain legumes and ensuring food security (2023)
Environmental stress generally causes considerable yield loss in leguminous crop production. This stress could be biotic (Insect pests, disease pathogens, weeds, vertebrate pests, etc.) or abiotic (Drought, heat, cold, salinity, flooding, heavy metal contamination, etc.). Either biotic or abiotic stress, both are capable of causing total yield loss. Unfortunately, crops are simultaneously exposed to these stress factors on the field. The response and level of tolerance to both stress factors, however, depend on the crop's genetic and nutritional status. The level of infection or infestation is determined by the cropping system and soil nutrient status. The induction of defense mechanisms by plants in response to pathogenic attack is dependent on environmental conditions like plant nutrient status. It means that there is a complex signaling network with crop nutrition that enables the plants to recognize and protect themselves against pathogens and other environmental stresses. The disease severity could be reduced by adequate crop nutrition due to host nutrient availability, plant composition of secondary metabolites, and the effect on the plant defense mechanisms. Shortages in essential nutrients on their own can predispose plants to attack by pests and pathogens. Therefore, the only sustainable method for growing crops in the face of different environmental stresses is good crop nutrition. A well-fed crop is more resistant to environmental hazards than poorly-fed crop. Though leguminous crops can fix atmospheric nitrogen themselves, the nutritional requirements for healthy crop production are more than just one element. The ability to fix nitrogen, if combined with appropriate crop nutrition will place the plant in a better position to withstand environmental stresses. This chapter discusses some of the different nutrient elements required by leguminous crops and their functions, crop nutrition abiotic stress tolerance, and mechanisms of nutrient-induced resistance in leguminous crops.